Exploring Well-Being Outcomes Among Persons Living with Dementia: Self-Reports Versus Caregiver Proxy Reports. (17th December 2021) - Minyo, Morgan; Powers, Sara; Ciancibello, Alyssa; Schaffer, Rachel; Bass, David
Abstract: A vast amount of research has focused on the development of dementia caregiving evidence-based programs (EBPs) in order to mitigate the well-known negative impacts of providing care for persons living with dementia (PLWD). In order to support efficacious results, many programs utilize a variety of both objective and subjective outcomes as typically reported by the caregiver or collected via medical history and clinical assessments. However, more recent research has attempted to understand the subjective illness experience of PLWD through self-report measures. Using data obtained from an online database (i.e., Best Practice Caregiving), that currently provides in-depth information on 44 dementia caregiving EBPs, the current study aimed to examine the number of EBPs that incorporated PLWD self-report measures on a variety of well-being outcomes. Results indicate that out of the 44 EBPs included for analysis: 1) Four out of 19 programs evaluating PLWD symptom severity/difficulty/distress used a PLWD self-report measure; 2) Eight out of 10 programs evaluating PLWD symptoms of depression used a PLWD self-report measure; 3) Five out of 10 programs evaluating PLWD quality of life/care utilized a PLWD self-report measure; and 4) One out of 9 programs evaluating ADL/IADL dependencies utilized a PLWD self-report measure. Discussion will focus on potential gaps and limitations of primarily using caregiver proxy reports to collect personal well-being outcomes for PLWD and ways in which researchers can integrate more self-report measures into intervention and programmatic evaluations.